(untitled) (American Journal of Islam and Society, 1999)
In Perspective This editorial seeks to identify the missing dimensions of Islamic economics and the Islamic dimensions of East Asian economies. In doing so, it advances a critical review of the present discourse on Islamic economics and highlights some of its oversights. At the outset, it must be clearly understood that I am not critical of the very idea of an Islamic economics. I think that at a time when global intellectual leadership has been usurped by those who consciously subvert the idea of the divine and the role of divine mandates in the organization and governance of human affairs, Islamic economics, like Islamic philosophy and Islamic social sciences, has succeeded in at least presenting a paradigmatic alternative that still maintaines the centrality of transcendence in human existence. While I am all for sustaining the resistance to secularization of all knowledges, I am critical of the current discourse on Islamic economics because of its disconnection between theory and practice and because, for reasons that have not been explored systematically but are intuitively discernable, it has made Islamic economics synonymous with’ interest-free banking. Many important elements of Islamic economics are completely ignored or even suppressed. Perhaps this may be a reason why Islamic economies have not really materialized. The importance of these less studied principles can be discerned by studying how they have played a cardinal role in the world’s fastest growing region, East Asia. I intend to show how East Asian economies have institutionalized Islamic principles in their contemporary economic practices and are harvesting great benefits. It is ironic that ...